MR CLEAN: Intra-arterial Intervention in Stroke Patients Is Safe and Effective. Issue 2 (11th March 2015) - Zarifyan, Alla
Results from the MR CLEAN clinical trial demonstrated that intra-arterial treatment within 6 hours of stroke onset in patients with acute ischemic stroke due to intracranial anterior occlusion was safe and effective at significantly reducing disability at 90 days, infarct volume at 7 days, and residual occlusion at 24 hours poststroke.